2004
DOI: 10.1097/01.inf.0000126901.88982.32
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster in Otherwise Healthy Children

Abstract: In normal infants and children, zoster can occur at any time after varicella or varicella vaccination. It is usually diagnosed clinically: a unilateral vesicular eruption following a dermatome or dermatomes. The incidence of zoster increases with age, although children who have had varicella during the first year of life (or in utero) are at increased risk of developing zoster. The incidence of zoster is less after varicella vaccination than after natural infection. Zoster in children is frequently mild, postz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
32

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 44 publications
1
61
0
32
Order By: Relevance
“…HZ infeksiyonu sağlıklı çocuklarda çoğunlukla 1-3 haftada sekelsiz iyileşme göstermesi nedeniyle HZ tedavisinde tek başına destek tedavisi yeterli olup, antiviral tedavi gereksinimi yoktur. Komplikasyon olarak kranial sinir tutulumu görülen, yaygın lezyonları görülen ve klinik olarak şiddetli seyir gösteren HZ olguları ile bereberinde immün yetmezlik, atopik dermatit gibi hastalıklar eşlik eden HZ olgularında antiviral tedavi önerilmektedir (12,13). Sonuç olarak, çocukluk çağı HZ enfeksiyonlarının altta yatan herhangi bir nedeni bulunamayan sağlıklı çocuklarda da görülebildiği, bizim olgumuz dahil birçok olguda rapor edilmiştir.…”
Section: Discussionunclassified
“…HZ infeksiyonu sağlıklı çocuklarda çoğunlukla 1-3 haftada sekelsiz iyileşme göstermesi nedeniyle HZ tedavisinde tek başına destek tedavisi yeterli olup, antiviral tedavi gereksinimi yoktur. Komplikasyon olarak kranial sinir tutulumu görülen, yaygın lezyonları görülen ve klinik olarak şiddetli seyir gösteren HZ olguları ile bereberinde immün yetmezlik, atopik dermatit gibi hastalıklar eşlik eden HZ olgularında antiviral tedavi önerilmektedir (12,13). Sonuç olarak, çocukluk çağı HZ enfeksiyonlarının altta yatan herhangi bir nedeni bulunamayan sağlıklı çocuklarda da görülebildiği, bizim olgumuz dahil birçok olguda rapor edilmiştir.…”
Section: Discussionunclassified
“…Benzer şekilde ülkemizde yapılan diğer bir çalışmada da %40 oranı ile kaşıntı en sık saptanan semptom olmuştur 10 . HZ'in en sık torakal (%75) ve lumbar (%11) dermatomları tuttuğu bildirilmiştir 2,9 . Bizim hastalarımızda da en sık torakal (%66,7) ve lumbar (%16,7) dermatom tutulumları gözlemlendi.…”
Section: Discussionunclassified
“…HZ, bir veya birkaç komşu duyusal sinirin dermatom alanına uyan deri bölgesinde veziküler lezyonlar ile karakterize bir durumdur. Çocukluk çağında oldukça nadirdir ve özellikle immünsüpresyonu olan hastalarda görülür [1][2][3] .…”
Section: Gi Riflunclassified
“…[16][17][18][19][20] The children who contracted varicella aged ,2 years had a significantly higher risk of developing childhood zoster than those contracting varicella aged $2 years (P , .001). This may be explained by a decreased level of immunity to VZV when varicella occurs at a much younger age.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has also been reported in otherwise healthy children, and most frequently in those with varicella infection in the first year of life. 1,7,[16][17][18][19] Several studies have indicated that exposure to VZV provides a protective effect against reactivation of VZV by boosting specific immunity to the virus. 20,21 Varicella vaccination programs have led to a reduction in the number of cases of varicella, and the reduced exposure to VZV may influence the incidence rates of HZ.…”
mentioning
confidence: 99%